APPLICATION OF AUGMENTED REALITY TECHNOLOGY IN THE ANIMATION OF THE KANCIL CHILDREN'S STORYBOOK - Suhendra Suhendra; Siti Aisyah; Fathan Mubina Dewadi (Jurnal Riset Informatika, 2021)
There are relatively many Indonesian fairy tales that are spread in the community, have characters with good and evil temperaments. Usually take folk tales about teaching goodness, behaving smartly, and being able to distinguish between good and bad. Also teaches children not to be arrogant, insulting other people. The learning process is usually in the delivery of material using only pictures, dolls, or videos that are commonly seen by children. Conventional media used for learning reduce children's enthusiasm. On this occasion, to answer the problem of media that is less attractive to children by using Augmented Reality (AR), because it can help visualize abstract concepts so that it can be used for understanding the image object and the structure of an object model. results of making applications using Augmented Reality, assessed from the aspects of cognitive, affective, psychomotor, technological, and the benefits of getting good interpretation results.